Alterations in ALK/ROS1/NTRK/MET drive a group of infantile hemispheric gliomas - Ana S. Guerreiro Stucklin (Nature Communications, 2019)
Infant gliomas behave differently to their childhood or adult counterparts. Here, the authors perform a large-scale genetic analysis of these tumours, revealing genetic alterations which may offer therapeutic opportunities.